ANALYSING THE IMPACT OF TECHNOLOGY INTEGRATION ON STUDENTENGAGEMENT AND LEARNING OUTCOMES IN K-12 EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Miftahul Jannah (Indonesian Journal of Education (INJOE), 2024)
Technology has become an essential part of modern education, especially at the K-12 level. Proper use of technology can greatly increase student interest and participation in learning. Students become more motivated and active in class when technology is used well and students' grades and problem-solving skills also improve. However, this success depends on several important factors, such as teachers' ability to use technology, students' access to devices and the internet, and support from the school. While there are some challenges, such as the risk of distractions and online safety issues, the benefits of using technology in education far outweigh them. It follows, then, that technology, when used appropriately, can be a highly effective tool for improving the quality of education at the K-12 level. It is important for schools and educators to develop good strategies for integrating technology into their curriculum to maximise students' learning potential in this digital age.